Analisis Pengaruh Tingkat Kesehatan Bank terhadap Profitabilitas (Studi Kasus pada Bank NTB Syariah Tahun 2020-2022) - Subangkit, Joko; Mulhimmah, Baiq Ratna; Azkar, Muh.; Amini, Titik Husnawati (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
This paper aims to determine whether there is any significant partial and simultaneous influence of CAR, FDR, NPF and BOPO ratios on ROA profitability at PT Bank NTB Syariah in 2020-2022. The sample used was 12 PT Bank NTB Syariah interim financial reports obtained through purposive sampling method. The method employed is a desk research analysis of the financial statements of PT Bank NTB Syariah. This research data is the secondary data of quarterly financial statements (Q1-Q4) during the 2020-2022 time period which is analyzed using hypothesis testing, namely Simple Linear Regression Analysis Partial t-test and Simultaneous F-test Multiple Regression Analysis. The most important result of this research is that there is no significant influence on CAR, FDR and BOPO on the ROA of NTB Syariah Bank. While NPF has a significant effect with Asymp. Sig. (2-tailed) of 0.028. Therefore, through the simultaneous F test, all financial ratios CAR, FDR, NPF, BOPO have a significant effect on the ROA of Bank NTB Syariah with an Asymp. Sig. (2-tailed) of 0.037. From the results of the ratio scores, it is known that the ROA of Bank NTB Syariah has a very healthy rating